EFEKTIVITAS KEBIJAKAN KARTU SANITASI DAN MODEL PELIBATAN ZAKAT DALAM LAYANAN SEDOT LUMPUR TINJA GRATIS DI KABUPATEN KARANGANYAR - Samsi; Widyantoro Yuliatmojo (Program Studi Ilmu Pemerintahan FISIP Universitas Galuh, 2021)
The rapid population growth and the rapid development of residential and industrial areas in several countries, including Indonesia, are increasingly adding to the burden and problems of domestic waste water. Because every day humans produce waste such as sludge, urine waste and other wastewater, which results in contamination of living bodies in the form of bacteria, fungi, and fungi that are pathogenic and produce toxins, this is very dangerous for human survival. This study aims to analyze the effectiveness of government policies and the involvement of zakat in free sludge suction services through the Sanitation Card (KARSA) model. This study uses a qualitative approach, with descriptive analysis techniques based on data and facts in the field. The results show that the APBD funds help low-income people and zakat funds help mosques, and are able to optimize the Fecal Sludge Treatment Plant (IPLT), in the KARSA program. Through the effectiveness of this policy, one step has succeeded towards the Sustainable Development Goals (SDGs) in 2030. namely the presence of sustainable sanitation for all, while Karanganyar Regency has received an award from the central government in the form of Drinking Water and Environmental Sanitation (AMPL) Award 2019